Las artes visuales como revitalización de los valores sociales : Caso testigo: Galpón Piedrabuenarte - Pellegrino, Marcelo (2018)
This Mega housing complex, Comandante Luis Piedrabuena, (erected in the 70s under the guidelines of modern-functionalist urbanism), houses 19,000 people in 2100 homes. Its particular location and the almost null relation with its surroundings, produces segregation and stigmatization of its inhabitants. It is interesting to analyze how they are resisted under the protection of a shed called "PIEDRABUENARTE" where diverse cultural activities are developed. There the neighboring artists have promoted the recovery of degraded public spaces, making murals on the walls of the courtyards and internal corridors of the buildings. This phenomenon, which arose as a response to segregation, revalues belonging and is a channel for the demand for decent housing and the right to popular culture.